Comparison of emergency department throughput and process times between male and female patients: A retrospective cohort investigation by the Reducing Disparities Increasing Equity in Emergency Medicine Study Group - Ege G. Onal; Kit Knier; Alexander W. Hunt; John M. Knudsen; David M. Nestler; Ronna L. Campbell; Kristine M. Thompson; Kharmene L. Sunga; Laura E. Walker; Bo E. Madsen; Annie T. Sadosty; Alyson J. McGregor; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Introduction Health equity for all patients is an important characteristic of an effective healthcare system. Bias has the potential to create inequities. In this study, we examine emergency department (ED) throughput and care measures for sex‐based differences, including metrics such as door‐to‐room (DTR) and door‐to‐healthcare practitioner (DTP) times to look for potential signs of systemic bias. Methods We conducted an observational cohort study of all adult patients presenting to the ED between July 2015 and June 2017. We collected ED operational, throughput, clinical, and demographic data. Differences in the findings for male and female patients were assessed using Poisson regression and generalized estimating equations (GEEs). A priori, a clinically significant time difference was defined as 10 min. Results A total of 106,011 adult visits to the ED were investigated. Female patients had 8‐min longer median length‐of‐stay (LOS) than males (P < 0.01). Females had longer DTR (2‐min median difference, P < 0.01), and longer DTP (5‐min median difference, P < 0.01). Females had longer median door‐to‐over‐the‐counter analgesia time (84 vs. 80, P = 0.58), door‐to‐advanced analgesia (95 vs. 84, P < 0.01), door‐to‐PO (by mouth) ondansetron (70 vs. 62, P = 0.02), and door‐to‐intramuscular/intravenous antiemetic (76 vs. 69, P = 0.02) times compared with males. Conclusion Numerous statistically significant differences were identified in throughput and care measures—mostly these differences favored male patients. Few of these comparisons met our criteria for clinical significance.